La motivación y su relación con el rendimiento académico, en el área de idioma extranjero, en estudiantes de educación secundaria de la l.E. "Francisco Izquierdo Rios" del distrito de Morales, en el año 2009. - Macedo Flores, Edwar (2011)
The research aimed to determine the relationship between motivation and academic performance in the area of foreign language in Grade 5 students of Secondary Education "FRANCISCO IZQUIERDO RÍOS", Morales District, in 2009, there were three specific objectives, a general hypothesis and three operational scenarios. The information was collected from 151 students, using a scale as a tool of motivation in leaming English and a data collection form to academic performance. The data obtained were processed using descriptive and inferential statistics. The hypothesis testing was carried out by comparing the correlation coefficient with the correlation parameters, considering that the relationship is direct when the coefficient is positive and the relationship is reversed when negative. According to Pearson correlation coefficient of direct correlation between motivation and academic achievement in the area of foreign language in the fifth grade students of Secondary Education "FRANCISCO IZQUIERDO RÍOS" located in Morales District, in 2009.